'Excavating' Pruitt-Igoe using space syntax. Issue 1 (March 2021) - Major, Mark David
Abstract : Pruitt-Igoe, in St Louis, Missouri, United States, was one of the most notorious social housing projects of the twentieth century. Charles Jencks argued opening his book The Language of Post-Modern Architecture, 'Modern Architecture died in St Louis, Missouri on July 15, 1972 at 3.32 pm (or thereabouts) when the infamous Pruitt-Igoe scheme, or rather several of its slab blocks, were given the final coup de grâce by dynamite.' However, the magazine Architectural Forum had heralded the project as 'the best high apartment' of the year in 1951. Indeed, one of its first residents in 1957 described Pruitt-Igoe as 'like an oasis in a desert, all of this newness'. But a later resident derided the housing project as 'Hell on Earth' in 1967. Only eighteen years after opening, the St Louis Public Housing Authority (PHA) began demolishing Pruitt-Igoe in 1972 [1]. It remains commonly cited for the failures of modernist design and planning.